Sign Language, Democracy and Deafness in Africa - and Okombo, Okoth (1999)
Abstract There is evidence all over the world that a sign language gives a deaf person the best chance of expanding one's space in life. Among those who have this awareness in Africa, there is a tremendous amount of enthusiasm to give the deaf people of Africa, as many sign language (SL) facilities as possible. The general line of thinking is that deafness is basically a communication disability, and that, if there are not compounding disabilities, a signing deaf person should have the same opportunities in life as an equally endowed hearing person, other factors kept constant. Yet even when this position is accepted, there are all sorts of questions that are left unresolved, e.g. What democratic institutions will guarantee such deaf-hearing equality? Where should the state come in and what space should be left to the deaf adults as an individual, and to the deaf-child's domestic care-givers? If the state cannot control what the deaf child gets at home, what repair mechanisms can be used to correct the damage done at home - without going against the canons of democracy? These and other issues of a similar nature will constitute the subject of this article.